2021
DOI: 10.3892/ol.2021.12717
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of the gastric cancer long non‑coding RNA‑associated competing endogenous RNA network

Abstract: Gastric cancer (GC) is a common type of cancer, and identification of novel diagnostic biomarkers associated with this disease is important. The present study aimed to identify novel diagnostic biomarkers associated with the prognosis of GC, using an integrated bioinformatics approach. Differentially expressed long non-coding RNAs (lncRNAs) associated with GC were identified using Gene Expression Omnibus datasets (GSE58828, GSE72305 and GSE99416) and The Cancer Genome Atlas database. A competing endogenous RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
4
2
0
Order By: Relevance
“… 55 , 56 LINC00501 , as an upregulated oncogenic lncRNA, was reported to distinguish GC from normal stomach tissues. 23 Consistent with this previous study, we reported that LINC00501 was significantly upregulated in GC tissues than in normal stomach tissues. Importantly, LINC00501 exhibited the further potential to identify advanced and metastatic GC; the AUCs of the ROC curve were 0.767 and 0.737, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“… 55 , 56 LINC00501 , as an upregulated oncogenic lncRNA, was reported to distinguish GC from normal stomach tissues. 23 Consistent with this previous study, we reported that LINC00501 was significantly upregulated in GC tissues than in normal stomach tissues. Importantly, LINC00501 exhibited the further potential to identify advanced and metastatic GC; the AUCs of the ROC curve were 0.767 and 0.737, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Emerging studies reported that lncRNA is a potential candidate biomarker for GC 55,56 . LINC00501 , as an upregulated oncogenic lncRNA, was reported to distinguish GC from normal stomach tissues 23 . Consistent with this previous study, we reported that LINC00501 was significantly upregulated in GC tissues than in normal stomach tissues.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A recent study demonstrated that GK-IT1 was a potential diagnostic biomarker for gastric cancer through bioinformatics analysis. 38 Our study demonstrated the clinical implication of GK-IT1 in ESCC. In addition, we showed that GK-IT1 could promote the proliferation and metastasis of ESCC cells for the first time.…”
Section: Discussionsupporting
confidence: 53%
“…Overexpression of FGF14-AS2 impaired the miR-205-5p induced phenotypic characteristics on proliferation, invasion, migration, and apoptosis in breast cancer cells [ 26 ]. It is identified that LINC01122 (cg09671962) is closely associated with OS coupled with a high risk of gastric cancer [ 27 ]. It was proved that MEG3 (cg14245102) can affect Wnt-β-catenin pathway and control epithelial-mesenchymal transition [ 28 ].…”
Section: Discussionmentioning
confidence: 99%